DIABETIC FOOT ULCER (DFU) PATIENTS’ PSYCHOLOGICAL REACTIONS ABOUT REOCCURRING DFU - Awuah-Baffour, Kwadwo (Acta Scientiae et Intellectus, 2024)
Foot ulcers are a problem for people with Diabetes Mellitus. Diabetes is a lifelong condition that can cause amputation, pain, stress, vision loss, and peripheral neuropathy. These factors cause psychological effects on the individuals through which they are stigmatized. These lead to financial burdens due to their inability to work efficiently and effectively. Frequent hospital visits and admissions deprive the patient and their families of the fullness of life. This literature review examines past research on the psychological effects of Diabetes Foot Ulcers (DFU). Research shows that the psychological impact of DFU is complicated, leading to poor quality of life. This review will focus on the various psychological factors that can cause a poor quality of life and suggest interventions to improve the patients’ quality of life.